SOME ISSUES OF IMPROVING THE LEGAL MONITORING IN THE REPUBLIC OF KAZAKHSTAN - Zarab Gazizovich Казиев (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article proposes measures to improve the legal monitoring in Kazakhstan.